Pelatihan dan Pembenahan Manajemen Keuangan dan Administrasi Pada Yayasan PAUD dan TK Musa Enda Padang - Ermatati Hatta; Rangga Putra Ananto; Armel Yentifa; Ulfi Maryati; Dita Maretha Rissi (Jurusan Akuntansi Politeknik Negeri Padang, 2018)
The use of money in the foundation must be accountable for the smooth achievement of educational goals. The purpose of financial management at the institution of education is to regulate all matters related to finance. Based on data that has good and adequate financial management and administration in accordance with applicable standards, it has not been applied to many PAUD Foundations and Kindergartens. So that the process of financial and administrative management has not been carried out properly and has resulted in a lack of accountability for school activities each period. The purpose of this service is to provide training and financial management and administration improvements to the PAUD Foundation and Musa Enda TK in the city of Padang. The expected result of this service is the existence of financial management and the improvement of good administration for the continuity of the school in the future.